Cultural Identity, Experience Quality and Revisit Intention to Mount Tai as A Heritage Tourism Destinations: Mediation Roles of Perceived Value, Perceived Destination Image and Satisfaction - Liu, Qi; Deeprasert, Jirawan; Jiang, Songyu (Journal of Ecohumanism, 2024)
The purpose of this research is to examine the effects of cultural identity, experience quality, and perceived value on tourists' revisit intention to Mount Taishan as a heritage destinations, and to investigate the roles of perceived destination image and satisfaction in influencing revisit intention, particularly to reveal satisfaction as a mediator between perceived value and revisit intention. Using a structured questionnaire survey, data were collected from 438 tourists who have the tourism experience in Mount Taishan. We then use structural equation modeling (SEM) approach to process the data analysis. The findings indicate that cultural identity, experience quality, and perceived value significantly influence revisit intention, with cultural identity showing the strongest effect. Furthermore, perceived destination image and satisfaction play crucial roles in shaping revisit intention, with satisfaction mediating the effect of perceived value. These insights underscore the importance of fostering a strong cultural connection, enhancing experience quality, and maintaining a positive destination image to promote sustainable repeat visitation at heritage sites like Mount Taishan.